2018
DOI: 10.1515/ntrev-2018-0083
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro morphological, optical and microbiological evaluation of nanosilver fluoride in the remineralization of deciduous teeth enamel

Abstract: BackgroundNanosilver fluoride (NSF) was developed as an alternative in the prevention of dental caries.PurposeThe aim of this study was to test the remineralizing action of NSF on incipient enamel caries and its antimicrobial action on the acid production and adhesion of Streptococcus mutans.MethodsDeciduous enamel fragments were treated with sodium fluoride (NaF), NSF and deionized water. Microhardness, fluorescence spectroscopy and optical coherence tomography imaging were performed on each specimen before c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…25,26 Vieira Costa and Silva et al evaluated the antibacterial and cytotoxic activity of NSF against Streptococcus mutans, and they found that NSF was a bacteriostatic and bactericidal compound with a similar antimicrobial property to SDF and low toxicity to living cells. 27 Further research can be conducted to evaluate the effect of fluoridated PEG-AgNPs on multi-species cariogenic biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Vieira Costa and Silva et al evaluated the antibacterial and cytotoxic activity of NSF against Streptococcus mutans, and they found that NSF was a bacteriostatic and bactericidal compound with a similar antimicrobial property to SDF and low toxicity to living cells. 27 Further research can be conducted to evaluate the effect of fluoridated PEG-AgNPs on multi-species cariogenic biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…33 Sodium fluoride with silver nanoparticles can act as a strategy for preventing and arresting caries. 17,18 Also, the addition of silver nanoparticles into restorative materials, such as adhesives and filling resins, can prevent secondary caries without compromising mechanical properties. 23,24 Silver nanoparticles can furthermore be utilized in orthodontic treatment to prevent initial caries by cooperating with adhesives, brackets, elastomeric ligatures, and removable retainers.…”
Section: Discussionmentioning
confidence: 99%
“…Sound enamel treated with nano silver fluoride has a similar value of microhardness to that of enamel treated with sodium fluoride. 18,19 The microhardness value of enamel caries treated with nano silver fluoride is higher than that of enamel caries treated with sodium fluoride. 20 However, the difference in the mineral content between nano silver fluorideand sodium fluoride-treated decayed enamel cannot be detected using optical coherence tomography.…”
Section: Effects Of Silver Nanomaterials On Enamel and Dentinmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Vieira Costa e Silva et al and Teixeira et al proved that the microhardness value of sound enamel surface treated by nanosilver fluoride is similar to that treated with sodium fluoride. (29,30) Furthermore, two separate clinical trials by Tirupathi et al and Dos Santos et al concluded that nanosilver fluoride has no effect on arresting the dentin caries in children. (31,32) Accordingly, further clinical studies are needed to accurately assess the nanosilver fluoride as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%